Screening and Identification of Key Biomarkers in Acquired Lapatinib-Resistant Breast Cancer - Bao, Shengnan; Chen, Yi; Yang, Fan; Sun, Chunxiao; Yang, Mengzhu; Li, Wei; Huang, Xiang; Li, Jun; Wu, Hao; Yin, Yongmei (Frontiers in Pharmacology, 2020)
Lapatinib, targeting the human epidermal growth factor receptor family members HER1 and HER2, 16 has been approved by the US Food and Drug Administration for use in metastatic HER2-positive 17 breast cancer. However, resistance to lapatinib remains a common challenge to HER2-positive 18 metastatic breast cancer. Until now, the molecular mechanisms of acquired resistance to lapatinib 19 (ALR) have remained unclear. With no definite biomarkers currently known, we aimed to screen for 20 key biomarkers in ALR. In this research, we identified 55 differentially expressed genes (DEGs, 20 21 upregulated, 35 downregulated) through bioinformatic analysis using microarray datasets GSE16179, 22 GSE38376, and GSE51889 from the Gene Expression Omnibus (GEO) database. The related gene 23 function was explored using the Gene Ontology (GO) function and Kyoto Encyclopedia of Genes 24 and Genomes (KEGG) pathway enrichment analysis. The protein-protein interaction (PPI) network 25 was constructed with the Search Tool for the Retrieval of Interacting Genes (STRING) and 26 Cytoscape. The functional enrichment of the DEGs was analyzed, including negative regulation of 27 the B cell apoptotic process, DNA replication, solute:proton symporter activity, synthesis and 28 degradation of ketone bodies, and metal sequestration by antimicrobial proteins. Analysis of seven 29 hub genes revealed their concentration mainly in DNA replication and cell cycle. Survival analysis 30 revealed that MCM10 and SPC24 may be related with poor prognosis in patients with ALR. 31 Meanwhile, the prediction model of lapatinib sensitivity was constructed, and emerging role of the 32 model was further analyzed using several webtools. In conclusion, hub genes are involved in the 33 complex mechanisms underlying ALR in breast cancer and provide favorable support for treatment 34 of ALR in future.